Endogenous merger formation in asymmetric markets: A reformulation and welfare analysis - Leslie Neubecker; Manfred Stadler (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2003)
This paper analyzes endogenous merger formation in oligopolistic markets where firms have different unit production costs. We reformulate the merger model, introduced by Barros (1998), by employing the core as cooperative equilibrium concept. We show that, depending on the size asymmetry in the pre-merger market, this alternative solution concept predicts a different post-merger market structure. For intermediate size differences, it is not the most efficient firm that is generally involved in the merger but the least efficient firm. Additionally, we present a welfare analysis which shows that under a wide range of size asymmetries, endogenous merger formation has a welfare improving net effect.
urn:nbn:de:bsz:21-opus-18741
Keywords: C71; G34; L41; 330; Asymmetric endogenous mergers; Coalition formation; Fusion; Oligopol; Core; Wohlfahrtseffekt; Theorie